A hybrid control scheme for a twin rotor system with multi objective genetic algorithm - Toha, Siti Fauziah; Tokhi, M. Osman (2010)
Control of vibration suppressions is crucial for applications in engineering particularly in the area of aircraft system. A hybrid control approach encompasses of using a feedforward intelligent command shaping technique with combination of intelligent PID feedback control is presented in this paper. The advantage of using command shaping is to reduce system vibration. However, it can cause delay in system response resulting to a conflict between vibration suppression and rise time response. Multi objective genetic algorithm is employ in this work to determine a set of solutions for the amplitudes and corresponding time locations of impulses on an extra sensitive (EI) command shaping as well as gain parameters for the PID controller. The effectiveness of the proposed technique is assessed both in the time domain and the frequency domain. Moreover, a comparative assessment of the performance of the technique with the system response and unshaped finite step input is presented.